Peran Organisasi Ikatan Pelajar Nahdlatul Ulama Ikatan Pelajar Putri Nahdlatul Ulama (IPNU IPPNU) Dalam Proses Pembinaan Karakter Pelajar Nahdlatul Ulama Di Desa Sumber Rejeki Karang Agung Ilir - Lita Resti Utami; Achmad Syarifudin; Irpinsyah . (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This research is entitled The Role of Nahdlatul Ulama Student Association and Nahdlatul Ulama Female Student Association (IPNU-IPPNU) in the Process of Character Development of Nahdlatul Ulama Students in Sumber Rejeki Village, Karang Agung Ilir District. This research aims to determine the role and supporting and inhibiting factors of the Nahdlatul Ulama Student Association (IPNU) and Nahdlatul Ulama Female Student Association (IPPNU) in character development of students. The focus of this research is how IPNU-IPPNU through its da'wah programs and activities is able to increase awareness, discipline, and religious values ​​in students, especially in the Nahdlatul Ulama environment such as through Makesta activities, PHBI, sholawat, and musyawarah. The research method used is qualitative with a descriptive approach. Data were obtained through interviews, observations, and documentation, then analyzed by data reduction, data presentation, and drawing conclusions. Informants in this study included the head of IPNU-IPPNU, members of IPNU-IPPNU, and the community of Sumber Rejeki Village. The results indicate several supporting and inhibiting factors in developing student character through the IPNU-IPPNU organization, namely technology, society, parental influence, genetics, and education. These factors contribute to shaping students' character, fostering noble morals, responsibility, and social awareness. Furthermore, the existence of IPNU-IPPNU serves as a strategic platform for instilling Islamic and national values ​​in a balanced manner. In conclusion, IPNU-IPPNU plays a crucial role as a student organization, serving not only as a medium for learning and organizing but also as an effective tool for character development. This research is expected to contribute to the development of da'wah strategies and the development of character education among students.